Field assessment of calcium, copper and zinc ions on plant recovery and disease severity following infection of Huanglongbing (HLB) disease - Ahmad, Khairulmazmi; Sijam, Kamaruzaman; Hashim, Habibuddin; Rosli, Zamri; Abdu, Arifin (Academic Journals, 2011)
The effect of Ca, Cu and Zn ions on plant recovery and disease severity following infection of huanglongbing disease was carried out at a commercial citrus orchards belonging to Lembaga Pertubuhan Peladang (LPP) Terengganu, situated at Durian Mentangau, Dungun, Terengganu. Application of Zn or Cu ions in combination with Ca was able to delay disease incidence and severity of hunglongbing disease. These treatments (C/Ca/Cu and C/Ca/Zn) also showed slightly reduction of AUDPC value on infected citrus trees. In general, analysis of macronutrients and micronutrients content in citrus leaves showed significantly different at the beginning of the study (0 to 6 months after treatment) but no significant different were observed at the end of the study period (6-9 months after treatment) as noted on Mg, P, Ca and Zn analysis. Results for specific leaf area showed no significant different among treatment as observed in leaf area, total leaf length and total leaf width. However, specific leaf area was increased gradually in all treatments over the period of the study. The overall results of field trial showed that infected citrus trees treated with combination of Ca and Zn ions at 600 and 10 ppm, respectively resulted in significant increase (P≤0.05) in terms of fruit production and total soluble solid (TSS) content only.